An application of grey wolf optimisation for combined heat and power dispatch. (2015) - Jayakumar, N.; Subramanian, S.; Elanchezhian, E.B.; Ganesan, S.
The purpose of this paper is to obtain the best feasible solution for combined heat and power dispatch (CHPD) problems. Being inspired by the hunting and searching behaviours of grey wolves, a swarm intelligence algorithm, grey wolf optimisation (GWO) has been developed and is used as an optimisation tool for the chosen problem. In addition to the nonlinear and non-convex operational characteristics of generating units, the practical operational constraints such as feasible operating regions of cogenerators, prohibited operating zones of thermal generators are considered. The GWO is implemented in the standard test systems for economic and combined economic emission dispatch operations. The obtained results are higher, feasible than or as good as the best known solutions by state-of-the-art algorithms reported in the literature. It is evident that the GWO attains a high quality solution to CHPD problems.